(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Liquid flow through fibrous materials is important in a diverse range of applications. The prediction of flow through fibrous materials is influenced by a variety of factors and has been recognized as a favorite topic of research in recent years. Capillary flow through fibrous materials takes place by two subsequent processes, known as wetting and wicking. Wetting of the material is the initial process, followed by wicking or flow through its capillaries. In high temperature and high humidity conditions, wicking through a textile fabric plays a very important role in maintaining the thermo-physiological comfort of the wearer by transferring the sweat from the skin to the outside surface of clothing. Prediction of the moisture transmission properties of fibrous materials is useful to characterize clothing comfort and it helps in designing textile fabrics with specific requirements. A variety of mathematical models have been proposed in order to understand the liquid flow characteristics of textile fabrics. Flow through capillary tubes and flow through porous structures have been the two main approaches taken by researchers in order to model the capillary flow through fibrous structures. This paper reviews the relevant research in the area of liquid moisture transmission through fibrous materials, followed by experimental verification of some predictions using some of the developed equations. This experimental verification was undertaken by the authors.